A Contribution on the Elucidation of the Electrooxidation Mechanism of Gentisaldehyde on a Glassy Carbon Electrode. Issue 14 (1st January 2016) - Brito, R. Estévez; Mellado, J. M. Rodríguez; Palma, A.; Montoya, M. Ruiz; Rodríguez-Amaro, R.; Mayén, M.
Abstract : The electrochemical behavior of gentisaldehyde (2, 5-dihydroxibenzaldehyde) on a glassy carbon electrode is studied by linear-sweep cyclic voltammetry finding one to three oxidation peaks, depending on both the number of cycles recorded and the pH, and one reduction peak. The oxidation product was the formyl-p-benzoquinone, generated by the oxidation of the biphenolic ring, and not the 2, 5-dihydroxybenzoic acid (gentisic acid) that could be formed by oxidation of the aldehyde group. The mechanism proposed at pH < pK1 (8.42) from the analysis of cyclic and convoluted voltammograms involves the loss of an H + ion from one hydroxyl group, a first quasi-reversible electron transfer to give a radical, and the release of a proton in a third step (the r.d.s.) followed by the second electron transfer to give the product. At pK1 < pH < pK2, the electroactive species is the anion that losses an ion H + to give the dianion, the process being of the CEE type (chemical-electrochemical-electrochemical steps). At pH > pK2 (10.93) the process becomes of the EE type (electrochemical-electrochemical steps), no H + ions being involved. Radicals species found justify the antioxidant capacity of gentisaldehyde.